Optimization of technology of Si-затравок for the production of поликристаллического silicon - Реков, Юрий Васильевич (Technology audit and production reserves, 2012)
In the articles described results of researches of technology of growing of затравок are from silicon (Si-growth) for the process of receipt of poly-silicon of electronic quality. Conformities to the law and thermal terms are studied which provide crystallizations of silicon of, high-quality descriptions of process of hydrogen renewal of chlorides of silicon. The method of implementation of express control of poly-silicon is offered on determination of maintenance of admixture of the coniferous forest